A Practical Model for Selecting Nonwoven Cover Date Bunch via Finite Element Analysis Using COMSOL Multiphysics - Guedri Wafa; Jaouadi Mounir; Msahli Slah (Journal of Natural Fibers, 2022)
Water injury and fungus infection are the main causes of large economic deterioration and losses in the quality of date fruits during harvesting period. The nonwoven bagging product was used for the first time on date palm and has been shown to efficiently protect date fruit from heavy rain and sunburn that reduces the rate of transpiration and increases fungus spoilage. The aim of this study is to evaluate the potential applicability of COMSOL code in simulating the heat transfer behavior through nonwoven date cover. The study also intended to use finite element method and adaptive mesh refinement technique to increase the accuracy of the solution and create model for efficient simulation of heat exchange in nonwoven bag. The proposed model was validated by the uniformity between simulating and experimental results. A detailed numerical study was conducted to find the influence of air permeability on heat transfer through nonwoven textiles. Results demonstrated that the reduction of nonwoven permeability is beneficial to minimize the heat taken away by forced convection by decreasing the inner air transportation.